Estrategias de afrontamiento del cuidador primario de pacientes con esquizofrenia en un centro de salud mental comunitario, Lima-2020 - Miranda Mesco, Mayra Carol (2021)
Background: As schizophrenia is one of the most disabling mental illnesses, it is the primary caregiver who meets the need for care. There is little research, within the framework of nursing care in mental health, that shows the coping of said caregiver as a fundamental axis of care, considering some strategies as adequate or inadequate for the process of adequate adaptation. Objective: To determine the coping strategies of the primary caregiver of patients with schizophrenia. Design: Descriptive study with a cross-sectional approach carried out in primary caregivers of patients with schizophrenia at the community mental health center “Renato Castro de la Mata”. Material and Methods: The population consisted of 30 primary caregivers of patients with schizophrenia who attended the health center and who met the selection criteria. Data collection was carried out through the Coping Strategies Inventory (CSI) instrument. The data were coded and then entered into a database created in the Ms Excel program for analysis with the statistical program Stata version 16.0. Results: The prevailing strategy was coping strategies focused on the problem with 90,0%, being the most used problem solving, and the least used cognitive restructuring. In strategies focused on emotions with 10%, being the most used emotional expression and the least used social withdrawal. Conclusions: Primary caregivers face the problem seeking its solution.